Species-soil relationships across Amazonia: Niche specificity and consistency in understorey ferns - Tuomisto, Hanna; Suominen, Lassi; Alonso, Alfonso; Cardenas, Glenda; Lehtonen, Samuli; Moulatlet, Gabriel Massaine; Perez, Eneas; Siren, Anders; Weigelt, Patrick; Zuquim, Gabriela (WILEY, 2025)
Aims: Knowledge about species niches along environmental gradients is needed to understand community assembly and spatial variation in floristic composition and species richness. In Amazonian rainforests, such knowledge is largely lacking, although ferns have been used to infer overall floristic and edaphic patterns. Here we explore fern species distributions along an important edaphic gradient, how narrow their realised niches are and how sensitive inferences are to species commonness, data quality and the region being sampled.
Location: Amazonia.
Methods: We used a large data set (1,215 transects across lowland Amazonia) to explore the realised niches of 54 species of two fern genera (Adiantum and Lindsaea) along a soil base cation concentration gradient. We used weighted averaging to estimate species optima and niche widths, and Huisman-Olff-Fresco modelling to assess species response shapes.
Results: Overall, species optima were rather evenly spread along the soil base cation concentration gradient, but Lindsaea optima were limited to the lower half of the gradient, whereas Adiantum optima were more often in the upper half. Most species had unimodal response curves. Mean niche width was ca. 25% of the observed gradient length for Adiantum and 17% for Lindsaea and was only weakly or not at all related to different aspects of species commonness. Species optima were robust to different modelling approaches and consistent across regional subsets. However, the central Amazonian data contained no transects with high soil base cation concentration, so species with high optima were either absent or obtained a lower optimum than in the NW and SW regions.
Conclusions: Our results support niche-related species sorting as an important process that defines species co-occurrence, turnover and richness patterns within Amazonian rainforests. All Adiantum and Lindsaea species, including the most abundant ones, had narrow enough realised niches to be considered useful indicators of edaphic and floristic variation within the rainforest.The niches of Amazonian ferns proved to be relatively narrow and clearly segregated along a soil base cation concentration gradient, giving rise to considerable species turnover. Lindsaea species were mostly on poor soils, Adiantum species on richer soils. Niche width was independent of species commonness, so even the most abundant species are useful as indicators of edaphic conditions.image